(untitled) (Third Sector Social Economic Review, 2021)
On August 21, 2020 President of the Republic of Turkey announced that natural gas reserves in the Black Sea. The efficient markets hypothesis claims that even the important public disclosures do not affect the stock prices of companies in semi-strong efficient markets. Discovered natural gas will have important effects on Turkish economy in the future. In this study, the short-term effects of the announcement are the subject of research. For this reason, the purpose of the study is to reveal the effect of this announcement made on August 21 on the stock returns of energy and oil companies operating in Borsa Istanbul via event study method. According to the results, it is concluded that the natural gas reserve disclosure in the Black Sea affected the stock returns of energy and oil companies. In addition, it can be said that Borsa Istanbul is not an efficient market in semi-strong form.